The metabolomic fingerprinting of four duku (Lansium domesticum) cultivars from Central Java, Indonesia based on unique metabolites and prospects for future breeding - ENDANG DEWI MURRINIE; FAZAT FAIRUZIA; NINDYA ARINI; HENY ALPANDARI; INGGIT MAHARANI (Society for Indonesian Biodiversity, 2024)
Abstract. Murrinie ED, Fairuzia F, Arni N, Alpandari H, Maharini I. 2024. The metabolomic fingerprinting of four duku (Lansium domesticum) cultivars from Central Java, Indonesia based on unique metabolites and prospects for future breeding. Biodiversitas 25: 3816-3839. This research aims to map the genetic identity of Central Java (Indonesia) duku cultivars, Sumber, Woro, Matesih, and Kalikajar, through a metabolomic analysis approach using the Gas Chromatography-Mass Spectrophotometer (GC-MS) method from duku fruit peel and flesh. Heatmap and principal component analysis (PCA) of volatile organic compound (VOC) metabolites identified from duku fruit peel grouped Sumber, Woro, and Matesih as one group, with Sumber and Woro being more similar, while Kalikajar was in a different group. The identified metabolites of duku fruit flesh show that Woro and Matesih cultivars are in the same cluster, followed by Kalikajar, which is closer to the Woro and Matesih metabolites. Sumber mostly has different metabolites. VOC metabolites successfully identified primary and secondary metabolites defined as common metabolites in four cultivars, which have a myriad of functions for plant growth and development, nutritional value, plant defense against biotic stress and environmental stress tolerance, and physiological plant phenotypes. The successful identification of these metabolites not only enhances our understanding of the duku cultivars but also reassures the accuracy and reliability of future breeding for superior duku plants that are resistant to biotic and abiotic stress based on the VOC metabolites in the Sumber, Woro, Matesih, and Kalikajar cultivars, particularly the unique metabolites that distinguish these cultivars.